PEMBERDAYAAN ANGGOTA KELOMPOK TANI HUTAN MANGROVE SEGARA BIRU DESA LONTAR TIRTAYASA PADA PELATIHAN PENGOLAHAN BUAH MANGROVE MENJADI KOPI MANGROVE - Saepudin, Saepudin; Ende, Ende; Hidayat, Ardi; Wijaya Kusuma, Jaka; Kurniawanto, Hadi; Suhandi, Suhandi (Jurnal Abdimas Bina Bangsa, 2025)
This community service activity focuses on the Segara Biru Mangrove Forest Farmers Group (KTH) community, Lontar Village in an effort to increase awareness of the use of natural resources, namely mangrove forests. The distribution of mangrove forests on the coast of Lontar Village, Tirtayasa District, Serang Regency, Banten Province has experienced an increase in 2018 and 2022. The recorded mangrove area in 2018 was 32.94 ha. Then the mangrove area will increase in 2022 by 39.12 ha. There has been an increase in area of ​​6.18 ha due to routine planting, perhaps in 2024 it will reach more than 42 ha. The aim of this service is for KTH members to have abilities or skills in the fields of production, management and marketing, and technology in processing mangrove fruit coffee. The method of this activity is holding technopreneur training, training to improve product quality and quantity, management and marketing training, as well as training to introduce the use of grinding machines, roasting machines, cutting machines and plastic packaging sealers. The results and discussion of the implementation of the activity are that the members of KTH Mangrove Segara Biru are able to process and produce mangrove fruit into mangrove coffee, are able to manage and market mangrove coffee both offline and online.